ART, DEPTH AND AFFECT IN "WINTER": METAMODERNIST CONTEXTS OF ALI SMITH’S NOVEL - ŠNIRCOVÁ, Soňa (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Art, Depth and Affect in Winter: Metamodernist Contexts of Ali Smith's Novel. The paper discusses Ali Smith’s Winter through the prism of the theory of metamodernism. The novel can be related to the works of authors who reject the cynical sophistication of postmodernist art and appropriate its strategies to focus on authenticity, sincerity, and affect. Drawing on Robin van den Akker, Alison Gibbons, and Timotheus Vermeulen, who maintain that the metamodernist structure of feeling manifests through a mix of/or oscillation between pre-modernist, modernist and postmodernist tropes and devices, the author considers Ali Smith’s novel a mixture of postmodernist, modernist and romantic elements and explores how these elements function in the production of the metamodernist effect of her novel. REZUMAT. Artă, profunzime și afect în Iarna: Contexte metamoderniste în romanul lui Ali Smith. Această lucrare se ocupă de romanul Winter de Ali Smith prin prisma teoriei metamodernismului. Acest roman poate fi asociat cu lucrările unor autori care resping sofisticarea cinică a artei postmoderniste și își însușesc strategiile postmodernismului pentru a se concentra pe autenticitate, sinceritate și afect. Bazându-se pe Robin van den Akker, Alison Gibbons şi Timotheus Vermeulen care susțin că structura metamodernistă a sentimentului se manifestă combinând și/sau oscilând între tropi și procedee pre-moderniste, moderniste și postmoderniste, autoarea apreciază că romanul lui Ali Smith este o mixtură de elemente postmoderniste, moderniste și romantice și cercetează modul în care aceste elemente funcționează în producerea efectului metamodernist al romanului. Cuvinte-cheie: metamodernism, Ali Smith, Winter, artă, profunzime, afect